Huomioita kansanperinteen tallentamisesta äänilevyihin. - Simonsuuri, Lauri (1949)
Résumé: Des observations sur la conservation de la tradition populaire par le moyen du phonographe.
jufo
Keywords: perinteenkeruu; kenttätyö; äänitteet; äänilevyt; perinnearkistot; traditionsinsamling; fältarbete; ljudupptagningar (produkter); grammofonskivor; traditionsarkiv; sound recordings -- archives -- fieldwork; folklore -- collecting -- sound recordings